Uptake of hormonal implants contraceptives compared to other forms of contraceptives in Abuja, Nigeria - Ayogu, Malachy E.; Eruemulor, Chibuzor C.; Olibe, Augustine O. (International Journal of Research in Medical Sciences, 2019)
Background: Subdermal implants are a long-term, efficacious, and easily reversible contraceptive with few adverse effects that pose no risk to the health of the users. It is increasingly accepted as a method of contraception in sub-Sahara Africa like ours. Despite this, its uptake in Nigeria has not reached optimum level. This study is aimed at evaluating the socio-demographic characteristics of subdermal implants users in Abuja, Nigeria, its acceptance rate, efficacy, and discontinuation rate. Methods: The case notes of all the women from the family planning unit were studied. Data on socio-demographic characteristics, uptake rate, side effects profile and the discontinuation rates between January 2013 and December 2017 were retrieved and analyzed using SPSS software and results expressed in numbers and percentages Results: Out of a total of 1,716 clients that were for contraception during the period under review, 786 accepted Jadelle/Implanon accounting for 45.8% of the implants acceptance rate. Of the 786 acceptors, 485(28.3%) chose Implanon, whereas 301(17.5%) preferred Jadelle. Discontinuation rate for both implants was 20.7%; the main reasons cited by the women were desire to have more children; 51(31.35%) and irregular vaginal bleeding; 30(18.4%). The Pearl Index for the implants in the study was zero. The peak parity for implant users was para 3. Approximately 72.1% the users of all forms of contraception were Christians, while 25.4% were Muslims. About 74.0% of the users had tertiary education. Conclusions: Jadelle/Implanon uptake was relatively high compared to other forms of contraception.